MAJAPAHIT CULTURE AS A PEDAGOGICAL TOOL: BRIDGING HISTORY AND LANGUAGE IN BIPA PROGRAMS - Panggalih, Wahyun Bardianing; Wibowo, Amiruddin Hadi; Muharlisiani, Lusy Tunik; Wafiroh, Laili Hibatin (Journal of Education and Research, 2024)
This study investigates the integration of ethnoliteracy strategies grounded in Majapahit culture within BIPA programs to enhance linguistic skills, intercultural awareness, and learner engagement. Employing a qualitative methodology, the research involved semi-structured interviews, reflective journals, and classroom observations to collect data from participants. Thematic analysis and triangulation were used to identify recurring themes and validate findings. Results indicate that the incorporation of Majapahit cultural elements, such as proverbs and folktales, significantly improved participants' language retention, practical application, and cultural empathy. Participants reported heightened motivation and a deeper connection to Bahasa Indonesia as a living language intertwined with history and cultural values. This study highlights the transformative potential of integrating local heritage into language education and offers practical implications for designing culturally responsive curricula in BIPA programs.